Extensive myocardial infarction complicated with stroke as the first presentation of HIV in A young sudanese male: A case report. (October 2022) - Fadelallah Eljack, Mohammed Mahmmoud; Nassir Mohammedali, Najla Fouad; Hussien Mohamed Ahmed, Kabab Abbasher; Ahmed, Omer Idris; Nour, Alshareef B.; Haroun, Mazin S.; Abdallah, Abdallah M.; Ibrahim Ali, Mustafa Mohamed
Abstract: Introduction: As it is a disseminated disease, HIV infection can be associated with significant cardiovascular and neurological complications; however, this commonly occurs late. Here, we highlight the unusual initial presentation of HIV infection, which is myocardial infarction complicated by stroke. Case presentation: A 30 years old male with a clear medical background presented with severe chest pain with evidence of ischemia on ECG and positive serum troponin. he received anti-ischemic drugs, and was prepared for coronary angiography with routine investigations tested positive for HIV; however, his condition was later complicated by stroke. Discussion: Antiretroviral medication, HIV disease characteristics, female gender, and HCV co-infection are risk factors for coronary artery disease (CAD) in HIV patients. Patients living with HIV are also at risk of developing stroke, which can be caused by atherosclerosis of the major arteries, small artery disease, cardiac embolism, CNS infections, coagulation issues, and non-atherosclerotic vasculopathy. Conclusion: The presentation of an acute coronary syndrome in a young patient should raise suspicion of uncommon causes and needs a prompt evaluation from digging up in history, detailed examination, and investigations with close follow-up to prevent the complications that may occur. on the other hand, known HIV Patients should be screened periodically with an electrocardiogram. Highlights: HIV infection can be associated with significant cardiovascular and neurological complications. The presentation of acute coronary syndrome in a young patient should raise suspicion of uncommon causes. Known HIV Patients should be screened periodically with electrocardiogram.